Relation between Type 1 Diabetes and Celiac Disease in Children - Tabassum Bashir, Zoha Rafaqat, Naveed Lodhi, Urooj Yahya (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This retrospective study aimed to investigate the association between Type 1 diabetes (T1D) and celiac disease in pediatric patients, examining the prevalence, clinical presentation, and laboratory findings in a cohort of children with both conditions. Methods: Medical records of 155 pediatric patients diagnosed with T1D at Nawaz Sharif Medical College in Gujrat were reviewed. Patients diagnosed with celiac disease either through serological tests or duodenal biopsies were included. Data on demographic characteristics, clinical symptoms, laboratory findings, and family history were collected and analyzed. Subgroup analysis was conducted to investigate associations between variables. Results: Among the 155 pediatric patients with T1D, 25 (16.1%) were found to have coexisting celiac disease. The clinical presentation included gastrointestinal symptoms such as abdominal pain and diarrhea, along with failure to thrive. Serological tests for anti-tissue transglutaminase antibodies were positive in all confirmed cases, and duodenal biopsies revealed characteristic histopathological changes. No significant correlations were observed between age at T1D diagnosis, family history of T1D or celiac disease, and the co-occurrence of both conditions. Practical Implication: This study will be helpful in finding the association of diabetes and celiac diseases in pediatric patients. Conclusion: This retrospective study highlights the significant association between T1D and celiac disease in pediatric patients, emphasizing the importance of early screening and detection for celiac disease in children with T1D. Healthcare professionals should remain vigilant in assessing gastrointestinal symptoms and growth patterns to optimize early diagnosis and appropriate management. Keywords: Pediatric, Patients, Diseases, TID